Siolmatra brasiliensis stem extract ameliorates antioxidant defenses and mitigates glycoxidative stress in mice with high-fat diet-induced obesity - Talpo, Tassiana Cristina [UNESP]; Motta, Bruno Pereira [UNESP]; Oliveira, Juliana Oriel de [UNESP]; Figueiredo, Ingrid Delbone [UNESP]; Pinheiro, Camila Graça [UNESP]; dos Santos, Carlos Henrique Corrêa; Carvalho, Mário Geraldo de; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (Elsevier, 2022)
Background: Obesity is accompanied by insulin resistance and glucose intolerance, which favor the onset of complications related to oxidative stress. The aim of this study was to investigate the effects and underlying mechanisms of hydroethanolic extract from Siolmatra brasiliensis stems on insulin resistance, glucose intolerance, advanced glycation end product (AGE) formation, and oxidative stress in mice with induced obesity. Methods: C57BL-6 J mice were fed a high-fat diet for 14 weeks and treated with 125 or 250 mg/kg S. brasiliensis extract during the last 7 weeks. The study assessed glucose tolerance and insulin sensitivity, lipid profile, plasma levels of thiobarbituric acid reactive substances (TBARS, biomarkers of oxidative damage), fluorescent AGEs (biomarkers of advanced glycation), and paraoxonase 1 (PON1) activity (antioxidant enzyme). The activities of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) in the liver and kidneys were also investigated. Results: Siolmatra brasiliensis extract had antiobesogenic effects; improved insulin sensitivity and glucose tolerance; decreased the total plasma cholesterol levels; decreased the levels of glycoxidative stress biomarkers, including AGEs (plasma, liver, kidneys) and TBARS (liver, kidneys); and also improved endogenous antioxidant defenses by increasing the activities of PON1 (plasma), SOD (kidneys), CAT (liver, kidneys), and GSH-Px (kidneys). Conclusion: This study expands on our knowledge about the pharmacological properties of S. brasiliensis and substantiates the potential of this plant species to be used as a complementary therapeutic agent to alleviate the metabolic dysfunctions resulting from dyslipidemia and glycoxidative stress.
Keywords: Advanced glycation end products; Antioxidant defenses; Cucurbitaceae; Lipid peroxidation; Obesity